+0  
 
0
65
1
avatar

I need to rewrite an equation so it has no fractions and I'm not sure how to do it. 

 Oct 21, 2021
edited by Guest  Oct 21, 2021
edited by Guest  Oct 21, 2021
 #1
avatar+391 
0

Hello Guest,

 

\(\frac{m}{m^2+5m-6}+\frac{2}{m+6}=\frac{1}{m-1}\) ,

 

\(\frac{m}{m^2+5m-6}+\frac{2}{m+6}-\frac{1}{m-1}=0\) ,

 

\(\frac{m}{m^2+6m-m-6}+\frac{2}{m+6}-\frac{1}{m-1}=0\) ,

 

\(\frac{m}{m*(m+6)-m-6}+\frac{2}{m+6}-\frac{1}{m-1}=0\) ,

 

\(\frac{m}{m*(m+6)-(m+6)}+\frac{2}{m+6}-\frac{1}{m-1}=0\) ,

 

\(\frac{m}{(m+6)*(m-1)}+\frac{2}{m+6}-\frac{1}{m-1}=0\) ,

 

\(\frac{m+2(m-1)-(m+6)}{(m+6)*(m-1)}=0\) ,

 

\(\frac{m+2(m-1)-m-6}{(m+6)*(m-1)}=0\) ,

 

\(\frac{2(m-1)-6}{(m+6)*(m-1)}=0\) ,

 

\(\frac{2m-2-6}{(m+6)*(m-1)}=0\) ,

 

\(\frac{2m-8}{(m+6)*(m-1)}=0\) ,

 

\(2m-8=0\) ,

 

\(2m=8\) ,

 

\(m=4\) ,

 

so the solution is \(m=4\) .

 

Straight

 Oct 21, 2021

10 Online Users

avatar